Effects of Educational Intervention on Maternal Knowledge Regarding Umbilical Cord Care of New-Borns - Tasleem Inayat, Samina Kausar, Mansoor Warriach, Zahid Anwer, Asma Khalid, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Worldwide, About 4 million children die during the neonate period. Major cause of 25 percent of these deaths is umbilical cord infection nearly 25% children die due to this reason, meanwhile 2/3 children are delivered at home and traditional umbilical cord done in under developed countries. Objective: The objective of this study was to assess the effect of educational intervention of maternal knowledge regarding umbilical code care. Study design: A quasi-experimental design. Material and Methods: The study was conducted in Institute of Nursing, The University of Health Sciences Lahore in collaboration with Fatima Memorial Hospital Lahore. The study population was the all expecting Primi gravida mothers who visited the Obstetrics and Gynecology outdoor department of Fatima Memorial Hospital Lahore. The whole sample size (100) was included in the study. Simple randomized sampling technique was used. The women included to the study in accordance with the inclusion criteria, all expecting primigravida mothers who were able to read and write Urdu or English language and had no psychological illness with the age range between 20-35 years were included in the study. SPSS was used for the statistical analysis. Results: The 66 % of the participants were under the age of 25-30 years whereas, 22 % were above the age of 30 years and only 12 % participants were below 25 years of age. As for their residence, all the participants belonged to urban area. Educational status of the participants revealed that more than half of the participants 30 % possessed higher secondary school education while, 36.7 % were with secondary education and about18 % had primary education. While the majorities 90 % were house wives and only 10 % were job holder. Conclusion: The Results of the present study indicate that overall impact of structural education intervention improves the maternal knowledge about newborns care.